STRUCTURE AND PROPERTIES OF DIALOGUE-QUESTIONING AS A MEANS OF FOREIGN PROFESSIONALLY ORIENTED COMMUNICATION OF ADMINISTRATIVE MANAGERS - Медведчук, А. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article analyzes the results of the study of English professionally oriented dialogue-questioningfeaturesfor administrative managers. The features of the process of learning English professionally oriented dialogue speech of administrative managers; taking into account differences in various types of dialogical unity and communicative situations are revealed. The main types of dialogues; depending on their communicative purpose; criteria; areas of communication and communication functions are reviewed. The structure of dialogue-questioning and the most common types of dialogical unity are identified. On the basis of thestudywe defined main requirements for formation of professionally oriented English communicative competence of administrative managers